A Case Study from Istanbul's Westernization Period: The Technical Documentation of Prinkipo Palace. Issue 2 (1st February 2022) - Somer, Melek Elif
ABSTRACT: The deterioration and the consequent collapse of historic timber structures lead to a significant loss of knowledge transfer of local construction methods and building technics. In this article, based on a case study of an exceptional timber frame structure in Istanbul dating from the end of the 19th century, is an attempt to provide documentation on the structure and materials of the specific building. The main objective is to underline the general structural system and materials as a reference. The case study covers the traditional characteristics such as local timber framework techniques and features of the transition era in construction and materials, with industrialized and standardized construction members.